Injuries, matches missed and the influence of minimum medical standards in the A-League professional football: A 5-year prospective study - Gouttebarge, V.; Hughes Schwab, B. A.; Vivian, A.; Kerkhoffs, G. M. M. J. (Asian Journal of Sports Medicine, 2016)
Background: Epidemiological data on the occurrence of time-loss injuries over several A-League seasons remains lacking, while the effect of the mandatory implementation of `Minimum Medical Standards` as a part of the collective bargaining agreement (CBA) needs to be explored. Objectives: To explore the 5 year evolution of hamstring, groin, knee, ankle and total time-loss injuries among professional footballers in the A-League; to evaluate the consequences of these time-loss injuries in terms of total matches missed and costs incurred; and to explore whether the mandatory implementation of `Minimum Medical Standards` in the A-League had led to a decrease in the occurrence of total time-loss injuries and total matches missed.